PERBEDAAN KADAR HEMOGLOBIN, NILAI HEMATOKRIT DAN JUMLAH ERITROSIT PADA STROKE ISKEMIK DAN STROKE HEMORAGIK DIFFERENCES OF HEMOGLOBIN LEVEL, HEMATOCRITE VALUE AND THE NUMBER OF ERYTHROCYTE IN ISCHEMIC AND HEMORRHAGIC STROKE - Annita Annita; Deswita Deswita; Al Kudri (Jurnal Kesehatan Medika Saintika, 2020)
Stroke merupakan penyebab utama kecacatan fisik pada usia produktif dan lanjut usia. Viskositas darah pada penderita stroke dapat dilihat berdasarkan hasil pemeriksaan hematologi darah berupa peningkatan kadar hemoglobin, nilai hematokrit dan jumlah eritrosit dari nilai normal yang dilakukan di laboratorium. Menilai kekentalan darah membantu penanganan stroke untuk mengurangi penyebaran kerusakan sel otak pada penderita stroke. Penelitian ini bertujuan untuk mengetahui gambaran kadar hemoglobin, nilai hematokrit dan jumlah eritrosit pada stroke iskemik dan stroke hemoragik. Desain penelitian adalah studi cross sectional. Penelitian ini dilakukan pada 60 subjek (30 pasien stroke iskemik dan 30 pasien stroke hemoragik) yang merupakan pasien IGD di RS Otak M. Hatta dari bulan Maret sampai Agustus 2020. Pemeriksaan kadar hemoglobin, nilai hematokrit dan jumlah eritrosit menggunakan Hematology Analyzer. Gambaran kadar hemoglobin, nilai hematokrit dan jumlah eritrosit pada pasien stroke iskemik dan hemoragik dengan uji-T independen, p <0,05 dianggap bermakna. Rerata kadar hemoglobin, nilai hematokrit dan jumlah eritrosit pada stroke iskemik lebih rendah (12,6±1,1/ gr/dl; 38±2,9/ %; 4,3±0,4/ million/mm3) daripada pada stroke hemoragik (15,2±0,1/ gr/dl; 45±2,7/ %; 5,1±0,4/ million/mm3). ABSTRACT Stroke is the main cause of physical disability in productive age and elderly. Blood viscosity in stroke patients can be seen based on the results of blood hematology examinations in the form of an increase in hemoglobin levels, hematocrit values and the number of erythrocytes from normal values carried out in the laboratory. Assessing blood viscosity helps stroke management to reduce the spread of damage to brain cells in stroke survivors. This study aimed to see a picture of hemoglobin levels, hematocrit values and the number of erythrocytes in ischemic stroke and hemorrhagic stroke. The research design was cross sectional study. This research was conducted on 60 subjects (30 patients with ischemic stroke and 30 patients with hemorrhagic stroke) who are IGD patient in M. Hatta Brain Hospital from March to August 2020. Hemoglobin levels, hematocrit values and erythrocyte count were examined using the Hematology Analyzer. A picture of hemoglobin levels, hematocrit values and the number of erythrocyte in ischemic and hemorrhagic stroke patients using an independent T-test, p <0,05 was considered significant. The mean rates of hemoglobin levels, hematocrit values and the number of erythrocytes were lower inischemic stroke (12,6±1,1/ gr/dl; 38±2,9/ %; 4,3±0,4/ million/mm3) than in hemorrhagic stroke (15,2±0,1/ gr/dl; 45±2,7/ %; 5,1±0,4/ million/mm3). There were significant differences in hemoglobin levels, hematocrit values and the number of erythrocytes in ischemic stroke and hemorrhagic stroke.